Omalizumab and Oral Immunotherapy in IgE-Mediated Food Allergy in Children: A Systematic Review and a Meta-Analysis - Enrico Vito Buono; Giuliana Giannì; Sara Scavone; Susanna Esposito; Carlo Caffarelli (Pharmaceuticals)
Background: Food allergies are a growing global health concern, particularly among children, with no widely approved curative treatment beyond strict allergen avoidance. Oral immunotherapy (OIT) has emerged as a promising strategy to induce desensitization, yet its implementation is limited due to high rates of allergic reactions and patient non-compliance. Omalizumab, a monoclonal anti-IgE antibody, has been proposed as an adjunct to OIT to enhance safety and efficacy. Objective: This systematic review and meta-analysis aim to evaluate the efficacy and safety of omalizumab in combination with OIT for IgE-mediated food allergy in children. Methods: A systematic literature search was conducted in PubMed/MEDLINE and Cochrane Central databases to identify randomized controlled trials (RCTs), controlled clinical trials (CCTs), and observational studies assessing omalizumab as an adjunct to OIT in pediatric food allergy. Studies were evaluated for desensitization rates, immunological changes, adverse events, and quality-of-life improvements. Results: OIT combined with omalizumab led to significantly higher rates of desensitization, allowing patients to tolerate higher doses of allergens in a shorter timeframe compared to OIT alone. Omalizumab was associated with a reduction in adverse reactions, including anaphylaxis, and improved treatment adherence. However, the long-term sustainability of tolerance post-omalizumab discontinuation remains uncertain. Conclusions: Omalizumab facilitates rapid and effective desensitization in pediatric food allergy, enhancing the safety of OIT. Further research is needed to determine optimal treatment duration, long-term outcomes, and cost-effectiveness before widespread clinical adoption.